EFFECT OF CATIONIC SURFACTANT ANTISEPTICS ON THE SOLUBILITY OF THE NATURAL POLYPHENOL CURCUMIN IN AQUEOUS SOLUTIONS - Lipkovska, N.O.; Barvinchenko, V.M.; Kartel, M.T. (Reports of the National Academy of Sciences of Ukraine, 2023)
The solubilization patterns, tautomeric transformations, and changes in the spectral characteristics of the natural polyphenol curcumin were investigated upon dissolution in aqueous solutions of cationic surfactant antiseptics, namely ethonium and decamethoxin. The effects were studied as a function of the concentration of the surfactants in solution. It was observed that curcumin predominantly dissolves in the enol form in the organized micellar media of these surfactants, resulting in a significant increase in its solubility by two orders of magnitude. Binding constants of curcumin with micelles of ethonium (lg Kb = 4.39) and decamethoxin (lg Kb = 4.47) were determined using the solubility method. In domicellar solutions of the long-chain cationic surfactant ethonium, prior to the formation of classical micelles, curcumin mainly dissolves in the ketone form, and its concentration increases by 150 times due to the formation of soluble supramolecular complexes. In contrast, the short-chain cationic surfactant decamethoxin has little effect on the solubility of curcumin and its keto-enol tautomeric equilibrium under the given conditions. The discovered patterns have significant scientific and practical implications for the development of drug formulations based on these systems.